PERAN APPROACHING TIME DALAM PENINGKATAN PELAYANAN JASA PEMANDUAN KAPAL DI PELABUHAN UTAMA TANJUNG PRIOK - Ika Citra Sari; Ruddy Suwandi; Arif Satria; Deni Achmad Soeboer (Fakultas Perikanan dan Ilmu Kelautan, 2016)
Approaching time is usually used as one of indicator on evaluating the successful of piloting’sservice level of ship in main port in Indonesia. However, in many main ports in some countries, this method is no longer used. This study is aimed to determine the significancy of approaching time as a standard in evaluating the piloting’s service in Indonesia.The research has been conducted in the Port of Tanjung Priok, where involved the respondents of pilotage personnels, ship captains, helmsman, and also some retired pilotage personnels which formerly have worked as pilotage. The data were analized using AHP (Analytical Hierarchy Process), AHP will describe the problem as multi-factor complex into a structured and systematic so easy to understand. The results showedthat 56.59% of respondences agree the approaching time is still important as an indicator on evaluating the service of pilotage, while 43.41% of them thought that it needs more considerations to use the approaching time as an evaluation indicator. It is important to note approaching time since it is a measurable workface in a shipping port in conducting the piloting service. This is caused that the pilotages still depend on the availabilities of all tools such astug boat in which the quantity and its capacity must still be raised again.